What Drives the Choice of Faith-Inspired Schools by Households? Qualitative Evidence - Gemignani, Regina (Taylor and Francis, 2014)
Why do some parents send their children to faith-inspired schools (FISs), while others choose to rely on public schools? Within FISs, are the motivations to send a child to a Christian school different from those to send a child to an Islamic school? How well are FISs performing—along various dimensions—according to the students’ parents? This article provides tentative answers to those questions using qualitative and small sample data collected in 2010 in Burkina Faso and Ghana.